UJI DAYA HAMBAT EKSTRAK ETANOL DAUN MAHKOTA DEWA (Phaleria macrocarpa Boerl.,) TERHADAP Klebsiella pneumonia. - Aulia Nur Rahmawati; Putri Afiana Solicah (Jurnal Ilmiah Manuntung, 2020)
Mahkota Dewa (Phaleria macrocarpa Boerl) is a medical plant of the Thymelaeaceae family originating from Indonesia, precisely from Papua. Phaleria macrocarpa Boerl the deity has been known in various treatments such as diabetes, cancer, liver, dysentery, allergic diabetes, eczema, or gout and others (Ratna & Wiwi, 2014). The purpose of this study is to find out whether extract ethanolic 96% of Phaleria macrocarpa Boerl can inhibit the growth of K. pneumoniae, and to know what concentration of extract ethanolic 96% of Phaleria macrocarpa goodnes to inhibit K. pneumoniae. The method used is the Kirby Bauer Method. With the average inhibition zone concentrations is 100%, 80%, 60%, 40%, 20% respectively 17.41mm, 15.37mm, 12.60mm, 11.10mm, 6.43mm.